A new species and a new record of Pelthydrus Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae) - Zhu, Bingyue; Ji, Lanzhu; Bian, Dongju (Zootaxa, 2018)
The members of the genus Pelthydrus are small-sized aquatic beetles which belong to the water scavenger beetle family Hydrophilidae. At present the lineage includes 63 valid species mainly occurring in Asia, with 21 known from China (Bian et al. 2008, 2009; Hansen 1999; Schönmann 1995). One new species is described here, which belongs to the Pelthydrus sculpturatus species group, bringing the total number of species within the group to seven (Schönmann 1995). One additional species is reported from China for the first time. Specimens were collected from Yunnan Province and are deposited in IAECAS (Institute of Applied Ecology, Shenyang, Chinese Academy of Sciences).